1997
DOI: 10.1074/jbc.272.44.27532
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin Targeting to the Regulated Pathway Is Not Impaired in Carboxypeptidase E-deficientCpe /Cpe Mice

Abstract: Sorting of proinsulin from the trans-Golgi network to secretory granules is critical for its conversion to insulin as well as for regulated insulin secretion. The proinsulin sorting mechanism is unknown. Recently, carboxypeptidase E (CPE) was proposed as a sorting receptor for prohormones. To know whether CPE is implicated in proinsulin sorting, pancreatic islets were isolated from CPE-deficient Cpe fat /Cpe fat mice and Cpe fat /؉ controls, pulse-labeled ([ 3 H]leucine), and then chased in basal medium (90 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 25 publications
3
64
1
Order By: Relevance
“…This view, however, is in contradiction with earlier studies showing that the N-terminal domain of POMC was not required for its sorting to the RSP but, rather, that cooperation between different internal POMC domains might be involved (21). Furthermore, the proposal of CPE as a sorting receptor for hormone precursors was recently challenged (22,23). Attention was also paid to the dibasic sequences that are usually numerous in prohormone precursors as possible sorting signals.…”
contrasting
confidence: 48%
“…This view, however, is in contradiction with earlier studies showing that the N-terminal domain of POMC was not required for its sorting to the RSP but, rather, that cooperation between different internal POMC domains might be involved (21). Furthermore, the proposal of CPE as a sorting receptor for hormone precursors was recently challenged (22,23). Attention was also paid to the dibasic sequences that are usually numerous in prohormone precursors as possible sorting signals.…”
contrasting
confidence: 48%
“…This proposal is based on studies examining the sorting of prohormones in the fat/fat mouse, and in cell lines that have a reduced level of CPE protein due to the expression of antisense RNA. However, proinsulin sorting is not dependent on CPE, based on studies of primary cultures of pancreatic beta cells (35) or the NIT3 beta cell line (21). The sorting of proinsulin and insulin into the regulated pathway of the beta cells proceeds in the complete absence of CPE from this pathway.…”
Section: Figmentioning
confidence: 99%
“…The precise mechanism by which these positively charged residues mediate secretion is unclear, although they have been suggested to interact with the acidic polar heads of phospholipids (63,64), possibly in lipid raft microdomains, or with enzymes that cleave or modify dibasic sites, including PCs and CPE, that could therefore act as sorting receptors (43). However, neither PC1, PC2, nor CPE seems to function as a general sorting receptor for all secreted hormones and neuropeptides; down-regulation of CPE in vitro or in vivo blocks regulated secretion of select hormones and growth factors (43,(65)(66)(67)(68), whereas distribution studies have identified cells that do not express either PC1 or PC2 yet secrete polypeptides via the regulated pathway (62).…”
Section: Discussionmentioning
confidence: 99%